Creating and Delivering Value in Marketing Proceedings of the 2003 Academy of Marketing Science (AMS) Annual Conference - Spotts, Harlan E.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
Founded in 1971, the Academy of Marketing Science is an international organization dedicated to promoting timely explorations of phenomena related to the science of marketing in theory, research, and practice. Among its services to members and the community at large, the Academy offers conferences, congresses and symposia that attract delegates from around the world. Presentations from these events are published in this Proceedings series, which offers a comprehensive archive of volumes reflecting the evolution of the field. Volumes deliver cutting-edge research and insights, complimenting the Academy’s flagship journals, the Journal of the Academy of Marketing Science (JAMS) and AMS Review. Volumes are edited by leading scholars and practitioners across a wide range of subject areas in marketing science.   This volume includes the full proceedings from the 2003 Academy of Marketing Science (AMS) Annual Conference held in Washington, D.C., entitled Creating and Delivering Value in Marketing.
Blueprinting and Strategy for Service Providers and Buyers -- Export Strategies and Global Markets -- Demographic Perspectives of Consumer Behavior -- European Perspectives on B2B Marketing -- Branding Decisions and Buyer-Seller Relationships in Global Markets -- Developments in Sales Management -- Advances in Research Methodology I -- e-Shopping and Website Loyalties -- The Internet, E-Commerce, and Marketing in LDCs -- EM Potpourri -- Marketing Implementation and Value Creation -- Ethics Responsibility -- Brand Issues: Image, Extensions and Relationships -- New Horizons in Business-to-Business Marketing -- Cross-Cultural Perspectives in International Marketing -- Advances in Research Methodology II -- Works-In-Progress: Ethics, Trust and Responsibility in a Dynamic Marketing Environment -- Controversial, Peer Recommendations, and Vulnerable Consumer Issues -- Modes of Online Value Creation -- Relationships and Trust in Buyer-Supplier Interactions -- New Trends in Education -- Price Promotion and Drivers on Customer Retentions -- How Consumers are Affected by Advertising and What They Believe as a Result -- Loyalty Issues -- Trust -- Commitment, e-Service Quality, Personal Value on Provider-Customer Relationships -- Behavioral Issues in Advertising, CRM, and Developing Economies -- Frameworks and Orientations for Investigating Retail Stores Images and C2C Dynamics -- Academy of Marketing Science Outstanding Teachers in Marketing -- CRM: Furthering Customer Relations -- Issues and Decisions in Emerging Markets -- The Contextual Interface of Online Consumption -- Emerging Issues in Business to Business Marketing -- Critical Evaluations of Educational Issues -- Chinese and Japanese Marketing Practices -- New Findings in Consumer Behavior and (Corporate) Brand Management -- Issues in Education -- Exploring Issues in Field Sales -- The Euro and the European Union: New Challenges for Marketing -- Cross-Cultural Comparisons -- Consumer Choice and Decision Making -- International Issues, Information Search, and Advertising -- Overseas Entry of SMEs, Service Marketers, and Joint Ventures -- Addendum to the 2002 Proceedings.
Keywords: Marketing; Leadership; Sales management; Marketing; Business Strategy/Leadership.; Sales/Distribution.